Novel Insight into the regulation of GSH Biosynthesis in higher plants - Rausch, Thomas; Gromes, Roland; Liedschulte, Verena; Müller, Ina; Bogs, Jochen; Galovic, Vladislava; Wachter, Andreas (Plant biology, 2007)
Abstract: In higher plants, the redox-active tripeptide glutathione (GSH) fulfills a plethora of functions. These include its pivotal role for maintaining the cellular redox poise and its involvement in detoxification of heavy metals and xenobiotics. Intimately linked to these functions, GSH also acts as a cellular signal, mediating control of enzyme and/or regulatory protein activities, either directly or via glutaredoxins. The redox potential of the GSH/GSSG couple is not only affected by the GSH/GSSG ratio but also by changes in GSH synthesis and/or degradation. As this couple operates as redox buffer in several cellular compartments, the regulation of GSH biosynthesis and transport (both intra- and intercellularly) are fundamental to the maintenance of cellular redox homeostasis during plant development and, even more so, when plants are exposed to biotic or abiotic stress. This review highlights novel aspects of GSH biosynthesis and transport with a focus on the regulation of the GSH1 (=γ-glutamylcysteine synthetase) enzyme. Interestingly, GSH1 appears to be exclusively confined to the plastids, whereas the second biosynthetic enzyme, GSH2, is predominantly localized in the cytosol. GSH1 expression and enzyme activity are under multiple controls, extending from transcriptional regulation to post-translational redox control. Now that the plant GSH1 protein structure has been solved, the molecular basis of GSH1 function and redox regulation can be addressed. The review concludes with a discussion of the simultaneous changes observed for GSH synthesis, transport, and metabolism during Cd-induced phytochelatin accumulation.